Evaluating The Impact Of Product Diversifcation On Financial Performance Of Selected Nigerian Construction Firms - Adamu, Nasiru; Zubairu, Ibrahim Khalil; Ibrahim, Yahya Makarf; Ibrahim, Aliyu Makarf (Penerbit Universiti Sains Malaysia, 2011)
The need for the improved performance and continuous survival of construction frms has caused frms to diversify into other businesses. The purpose of this study is to determine the inﬂuence of diversifcation on the performance of some Nigerian construction frms. Financial statements from seventy construction frms were analysed. The specialisation ratio method was used to measure and categorise the frms into undiversifed, moderately diversifed and highly diversifed frms, and proftability ratios were used to measure the group-wise performance of the frms. The Student t-test was used to test the relationship between the extent of diversifcation and performance. The fndings reveal that undiversifed frms outperform the highly diversifed frms in terms of Return on Total Assets and Proft Margin. Similarly, the moderately diversifed frms were found to outperform the highly diversifed frms in terms of Return on Equity, Return on Total Assets and Proft Margin. However, no performance difference was found between the undiversifed frms and the moderately diversifed frms based on the three measures used. A nonlinear relationship was found between the extent of diversifcation and performance. It was concluded that diversifcation does not necessarily lead to an improvement in proftability. The implication is that frms are better-off remaining focused if the aim is to improve fnancial performance.